Social Marketing Communication of Peace Education Program by Peace Generation Indonesia - Nabilla Anasty Fahzaria; Neni Yulianita; Anne Ratnasari (Unisba Press, 2022)
Indonesia is a multicultural country that every year has reports of increasing rates of intolerance and a high potential for conflict. So that peace education is needed to prevent it. Peace Generation Indonesia or PeaceGen is a Non-Government Organization (NGO) working in the field of peace based in Bandung. The activities they do include the development of peace training through creative media and game-based learning, creating peace learning media, and activating peace content. PeaceGen has also produced more than forty thousand Agents of Peace (AoP) to spread peace. This study aims to find out the social marketing communication activities carried out by Peace Generation by reviewing and analyzing program design, promotion mix implementation, utilization of the “AoP Journey” digital platform, and the role and ability of the Agent of Peace Coordinator in fostering relationships with the Agents of Peace. This research uses qualitative methods and a case study approach. The results of the study show that the marketing communication carried out by Peace Generation seeks to produce peace education using collaborative programs and collective actions to create a peace-loving society. However, the use of digital platforms in their activities still allows for technological gaps.